2020
DOI: 10.3390/s20040956
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Attention Fusion for Obstacle Detection Using MmWave Radar and Vision Sensor

Abstract: For autonomous driving, it is important to detect obstacles in all scales accurately for safety consideration. In this paper, we propose a new spatial attention fusion (SAF) method for obstacle detection using mmWave radar and vision sensor, where the sparsity of radar points are considered in the proposed SAF. The proposed fusion method can be embedded in the feature-extraction stage, which leverages the features of mmWave radar and vision sensor effectively. Based on the SAF, an attention weight matrix is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 45 publications
(126 reference statements)
1
83
0
Order By: Relevance
“…These algorithms project radar data to image coordinate system. Moreover, as it is known that radar data is sparse compared with image, these algorithms try to make the best of different dimension information of radar measurement, such as distance, speed, and intensity to fill multiple channels of “radar sparse image” [ 26 ]. Multi-frame data is also used here to increase the density of radar data [ 25 ].…”
Section: Mmw Radar Perception Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…These algorithms project radar data to image coordinate system. Moreover, as it is known that radar data is sparse compared with image, these algorithms try to make the best of different dimension information of radar measurement, such as distance, speed, and intensity to fill multiple channels of “radar sparse image” [ 26 ]. Multi-frame data is also used here to increase the density of radar data [ 25 ].…”
Section: Mmw Radar Perception Approachesmentioning
confidence: 99%
“…Thirdly to address the unbalance between positive and negative samples, focal loss is adopted to design the loss function. [ 26 , 75 ]. Under multifaceted efforts, deep fusion networks reveal their good performance as is showed In Table 2 .…”
Section: Mmw Radar Perception Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the studies of predicting a driver's attention locations have shown dramatic progress, owing to the development of deep convolutional neural network frameworks [10][11][12][13]. Existing attention prediction approaches based on deep neural networks leverage semantic segmentation networks that predict a class label among a set of predefined class labels for each pixel of an image.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have developed solutions based on machine learning (ML) or deep learning (DL): Algabri and Choi, [ 28 ] present a method to detect and track people in indoor environments, whereas Qiu et al [ 29 ] focused on different types of moving obstacles in outdoor environments. More recently, other authors, Chang et al [ 30 ], Yang et al [ 31 ] and Qiu et al [ 32 ] have developed solutions for obstacles detection for self-driving cars. However, the main drawback of these solutions based on ML/DL is that, most of them, require a lot of training and thus existing data.…”
Section: Introductionmentioning
confidence: 99%